Pai Learning in The Implementation of Religious Culture (Spiritual Intelligence in Senior High School Students in Meranti Islands Regency) - Amrul Amrul; Mas’ud Zein; Edi Yurianto (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze Islamic Religious Education (PAI) learning in the implementation of religious culture among students of State Senior High Schools (SMA) in Kepulauan Meranti Regency. The main focus of this study is the development of students' spiritual intelligence through an integrative approach that combines aspects of formal learning, religious cultural values, and daily spiritual activities. The research method used is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the implementation of religious culture has a positive impact on increasing students' spiritual intelligence, which can be seen from their religious attitudes, understanding of moral values, and self-reflection skills. This study concludes that PAI learning integrated with religious culture can be an effective strategy in building a young generation that is religious and has high morals.